How Does Globalization Affect the Synchronization of Business Cycles? - Kose, M. Ayhan; Prasad, Eswar S; Terrones, Marco E (American Economic Review, 2003)
How Does Globalization Affect the Synchronization of Business Cycles? by M. Ayhan Kose, Eswar S. Prasad and Marco E. Terrones. Published in volume 93, issue 2, pages 57-62 of American Economic Review, May 2003